Analisis Bibliometrik Literasi Keuangan dan Bela Negara dalam Penggunaan Paylater - Ramadhan, Brian Bayu; Yuhertiana, Indrawati (Jurnal Informatika Ekonomi Bisnis, 2025)
This research aims to map the problems of Financial Literacy and Defence of State in the use of Paylater. This research aims to investigate current issues related to the topic using 997 articles from the Google Scholar database spanning the years 2018 to 2023. The study utilizes bibliometric methods with VOSviewer software version 1.6.20 to visualize the research analysis. The analysis includes four metrics: citation analysis, co-citation analysis, bibliographic coupling, and keyword co-occurrence. This mapping analysis reinforces the concept of state-run accounting at the individual level with the presence of the phenomenon of ease of transaction using the paylater model. The results of the analysis showed that there are seven research clusters related to the keyword Financial Literacy and the Defence of the State. The seven cluster are religiousness, martial education, empowerment of the village economy, the role of community institutions, the financial challenges of students in urban areas, the performance of sharia banking and high school education in Malang city.